2018
DOI: 10.1016/j.brainresbull.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Pilocarpine/ascorbic acid interaction in the immature brain: Electrophysiological and oxidative effects in well-nourished and malnourished rats

Abstract: Ascorbic acid (AA) administration has been associated with neuroprotection against oxidative stress, although at high doses it can facilitate oxidation and acts like a proconvulsing drug. The pilocarpine-induced epilepsy model has been widely studied. However, less is known about the effects of sub-convulsive doses of pilocarpine on brain activity in immature animals under normal or deficient nutritional conditions. Herein, we investigated the effects of chronic pilocarpine administration in a sub-convulsive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 69 publications
4
5
0
Order By: Relevance
“…This finding confirms previous data indicating that substances with anticonvulsant activity (e.g., dipyrone; Doretto et al, 1998 ) enhance the CSD velocity ( Amaral et al, 2009 ). Moreover, these data are similar to previous findings showing that low and high doses of the antioxidant vitamin ascorbic acid decelerated and accelerated CSD, respectively, in rats ( Mendes-da-Silva et al, 2014 , 2018 ). Taken together, these findings are in accordance with the idea that the CSD, as an interesting phenomenon, can help in extending our knowledge about the involvement of redox imbalance into the pathogenesis of neurological diseases ( Guedes et al, 2012 ) with the possible involvement of astrocytes ( Torrente et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…This finding confirms previous data indicating that substances with anticonvulsant activity (e.g., dipyrone; Doretto et al, 1998 ) enhance the CSD velocity ( Amaral et al, 2009 ). Moreover, these data are similar to previous findings showing that low and high doses of the antioxidant vitamin ascorbic acid decelerated and accelerated CSD, respectively, in rats ( Mendes-da-Silva et al, 2014 , 2018 ). Taken together, these findings are in accordance with the idea that the CSD, as an interesting phenomenon, can help in extending our knowledge about the involvement of redox imbalance into the pathogenesis of neurological diseases ( Guedes et al, 2012 ) with the possible involvement of astrocytes ( Torrente et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…The present study extends the previous observations of our group on the effects of taurine (Francisco and Guedes, 2015) and pilocarpine (Mendes-da-Silva et al, 2018) in rats of a younger age (PND7-27) than our rats (PND35-55). Analyzing such effects at another age might be of importance, regarding the time course of drug actions (Guedes and Abadie-Guedes, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…and gavage; n = 10 L 9 and 8 L 15 rats); (3) Taurine (300 mg/kg/day via gavage; n = 9 L 9 and 9 L 15 rats), as previously described (Francisco and Guedes, 2015); (4) Pilocarpine (45 mg/kg/day via i.p. ; n = 9 L 9 and 10 L 15 rats), following Mendes-da-Silva et al (2018); (5) Taurine plus pilocarpine (300 mg/kg/day via gavage and 45 mg/kg/day via i.p, respectively; n = 8 L 9 and 11 L 15 rats). Scopolamine methyl nitrate, a muscarinic receptor antagonist, was administered (1 mg/kg/day via i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we demonstrated that the non-carotenoid antioxidant alpha-tocopherol also antagonizes the effect of ethanol on CSD, suggesting that this antagonistic action is not a particular property of carotenoids (Abadie-Guedes et al, 2016). In line with this suggestion, it is interesting to note that another non-carotenoid antioxidant molecule, ascorbic acid, has been shown to modulate CSD (Mendes-da-Silva et al, 2014, 2018).…”
Section: Electrophysiological Effects Of Aging: Studies Using the Sprmentioning
confidence: 59%